Effects of 450 MeV Kr Swift Heavy Ion Irradiation on GaN-Based Terahertz Schottky Barrier Diodes - Yan Ren; Yongtao Yu; Shengze Zhou; Chao Pang; Yinle Li; Zhifeng Lei; Hong Zhang; Zhihong Feng; Xubo Song; Honghui Liu; Yongli Lou; Yiqiang Ni (Micromachines)
GaN-based terahertz (THz) Schottky barrier diodes (SBDs) are critical components for achieving high-power performance in THz frequency multipliers. However, the space applications of GaN-based THz SBDs are significantly constrained due to insufficient research on the effects of space irradiation. This work investigates the effects of 450 MeV Kr swift heavy ion (SHI) irradiation on the electrical characteristics and induced defects in GaN-based THz SBDs. It was found that the high-frequency performance of GaN-based THz SBDs is highly sensitive to Kr SHI irradiation, which can be attributed to defects induced in the GaN epitaxial layer by the irradiation. Low-frequency noise analysis reveals trap states located at an energy level of approximately 0.62 eV below the conduction band. Moreover, the results from SRIM calculation and photoluminescence spectra confirmed the presence of irradiation-induced defects caused by Kr SHI irradiation.